(Invited) Development of in situ Electrochemical Small-Angle Neutron Scattering (eSANS) for Simultaneous Structure and Redox Characterization of Nanoparticles. (26th April 2016) - Prabhu, Vivek M; Reipa, Vytas; Rondinone, Adam J; Formo, Eric; Bonnesen, Peter V
Abstract : An in situ electrochemical small-angle neutron scattering (eSANS) method was developed to measure simultaneously the redox properties and size, shape and interactions of solution-dispersed nanomaterials. By combining multi-step potentials and chronocoulometry readout with SANS, the structure and redox properties of engineered nanomaterials are followed in one experiment. Specifically, ZnO nanoparticles were examined as dilute dispersions in pH buffered deuterium oxide solutions under negative electrode potentials. The ZnO disk-shaped nanoparticles undergo an irreversible size transformation upon reduction at the vitreous carbon electrode. The decrease in average nanoparticle size near a current maximum shows the reduction reaction from ZnO to Zn occurs. The eSANS method provides nanometer scale sensitivity to nanoparticle size and shape changes due to an electrochemical reaction that is crucial to understand in energy, healthcare, and other applications.